Adolescent with groin pain: case report - Daniela Couto; José R. Oliveira; Bárbara Choupina; Mafalda Santos (Publicaciones Permanyer, 2024)
Introduction: Avulsion fractures are common in skeletally immature athletes and occur more often in the proximal femur and in the iliac bone. An avulsion fracture of the lesser trochanter is a rare pathology, and it results from a sudden and violent muscle contraction of the iliopsoas muscle during sports practice. Radiography is important for the diagnosis and exclusion of other pathologies. In most cases, symptomatic treatment is recommended, and surgery is reserved for specific situations. Case report: We report a clinical case of an adolescent with groin and right thigh pain and impaired gait after kicking a ball during a football match. Discussion: The patient underwent a radiographic study, and an avulsion fracture of the lesser trochanter was diagnosed. He was successfully treated with a conservative approach and no sequelae were documented.